Axillary adipose tissue–derived lymphatic endothelial cells exhibit distinct transcriptomic signatures reflecting lymphatic invasion status in breast cancer - Asumi Iesato; Jun Suzuka; Kazutaka Otsuji; Tomo Osako; Nami Yamashita; Yuka Inoue; Tetsuyo Maeda; Natsue Uehiro; Kazuyo Yoshida; Yoko Takahashi; Kohei Kumegawa; Sumito Saeki; et al. (Breast Cancer Research)
Abstract Background Lymphatics provide a route for breast cancer cells to metastasize. Lymphatic endothelial cells (LECs), which form the structure of lymphatic vessels, play a key role in this process. Although LECs are pivotal in cancer progression, studies often rely on commercially available cell lines that may not accurately reflect the tumor microenvironment. Therefore, there is a pressing need to directly study patient-derived LECs to better understand their role in breast cancer. Methods This study developed a method to isolate and characterize LECs directly from human breast-to-axilla adipose tissue. We used magnetic cell separation to remove CD45 + leukocytes and fluorescence-activated cell sorting to isolate cells expressing CD31 and podoplanin. Isolated cells were cultured under conditions promoting endothelial cell growth and were characterized through various assays assessing proliferation, tube formation, and gene expression patterns. Results The sorted CD31 + /PDPN + /CD45 − cell populations exhibited marked increases in proliferation upon VEGF-C stimulation and formed tubule structures on BME-coated dishes, confirming their LEC properties. Notably, isolated LECs showed distinct gene expression patterns depending on the presence of lymph node metastasis and lymphatic invasion. Conclusions The ability to isolate and characterize patient-derived LECs from mammary adipose tissue offers new insights into the cellular mechanisms underlying breast cancer metastasis. Significant gene expression variability related to disease state highlights the potential of these cells as biomarkers and therapeutic targets. This study emphasizes the importance of using patient-derived cells to accurately assess the tumor microenvironment, potentially leading to more personalized therapeutic approaches.